End-to-end fully-informed network nodes associated with 433 MHz outdoor propagation environment - Abubakar, Adamu; El-Gammal, Mohamed Tarek; Alarood, Ala Abdusalam (University of Bahrain, 2022)
Internet of Things (IoT) is operationally defined in this study as “an end-to-end fully-informed network associated with 433 MHz outdoor propagation environment”. The work is motivated by the fact that minimizing delay and transmission time is crucial to maintaining fully-informed network under 433 MHz propagation. This is intended to answers two questions: “how transmission delay affect early detection of network failure:” and “how faster is necessary to recover from a network failure?”. Endto- end fully-informed network was designed and constructed. An experimental analysis for data transmission on the network were performed. The experimental analysis has shown that the antenna height and the distance between transmitter and receiver have the most effective impact on the transmission success. Furthermore, the high rate bandwidths have shown a negative effect on the data integrity and total dysfunctionality above 50 meters. Thus, in end-to-end fully-informed network, it is revealed that transmitting more than 8 KB (at both 57600 bps and 115200 bps) has a drawback in end-to-end fully-informed network. However, transmission over 80 meters the most stable bandwidth that keeps the data integrity in end-to-end network is (9600 bps). Experimental analysis reveals that delay is thus reduced as well as transmission times increases.